The low level of biology teacher candidate questioning skills - D. Darmadi; Riki Apriyandi Putra (University of Muhammadiyah Malang, 2020)
Questioning skills is one of competencies required by teachers in dealing with the 21st-Century challenges. The purpose of this study was profiling biology teacher candidates’ questioning skills in Pekanbaru. The subjects of the research were the students, in three institutions, who were taking Zoology course. The total number of the subjects were 278 students selected using purposive random sampling. The instrument used was test contained of five items which instructed students to make questions related to five objects. The results showed that the teacher candidates’ question level in three institution were low-level question (more than 50% in C1-C3 level). The questions posed were dominance in the level of memorizing, understanding, applying, and analyzing. They were not accustomed to asking questions with the evaluating and creating levels. The systematic of question was dominated as a divergent question, while the question area asked was dominated in the physiology (32.93%) and morphology (32.14%) concept. The information gained from this study can be consideration point for further research.